Construindo o estágio de docência da pós-graduação em química - Feitosa,Judith P. A. (2002)
The teaching apprenticeship established by CAPES for post-graduation scholarship beholders has been discussed and the criterion adopted for the implementation in the post-graduation in Inorganic Chemistry Program presented. A teaching plan for the new subject is proposed, based on the experience gained through a first group. An instrument for evaluation of the student's performance has been developed and analyzed. Aspects like knowledge, clearness, enthusiasm, confidence, good manage on the audio-visual resources, class length are mentioned by degree of importance and the major difficulties faced and pointed out by the students.